Characterising the killing of girls and women in urban settings in Latin America, 2000-2019: an analysis of variability and time trends using mortality data from vital registration systems - Brisa N Sánchez; Heidi Stöckl; Yvonne L Michael; Nina Sun; Dèsirée Vidaña-Pérez; Ana Ortigoza; Amelia Augusta de Lima Friche; Mónica Mazariegos; Bricia Gonzalez Trejo; Catalina Correa-Salazar; Vanessa DiCecco (BMJ Publishing Group, 2024)
Introduction Latin America is burdened by high levels of violence. Although boys and men often experience more violence and fatalities, girls and women face a greater risk of being killed by family members or intimate partners due to their gender, a phenomenon known as femicide. Our study estimates femicide rates in Latin America across age groups, examining city-level variations and temporal trends.Methods Utilising data from the Salud Urbana en America Latina project, we analysed mortality data from 343 cities in nine countries between 2000 and 2019. We calculate the variability between and within countries using data from 2015 to 2019. We then describe time trends using femicide counts by year and city and fitting a three-level negative binomial model with a random intercept for country, fixed effects for age categories, and city-level and country-level random slopes for time (scaled to decades). Finally, we assess longitudinal time trends by age by including an interaction term for age and time (scaled to decades).Results Our results highlight substantial heterogeneity in femicide rates within and between countries. Additionally, we find that women 15-29 and 30-44 years of age experience the highest femicide rates across all countries. While our findings suggest a slight decline in femicide rates per additional decade (RR 0.95, 95% CI: 0.74 to 1.24) between 2000 and 2019, the trends diverge in different countries, suggesting increasing rates in some countries like Mexico. Age-specific trends suggest the persistence of higher rates among women 15-29 and 30-44 years of age over time.Conclusion We underscore the need to consider gender dynamics in understanding and preventing femicides, focusing on city-level interventions to address the multifaceted causes of violence against girls and women in the region.